Analisis Implementasi Kebijakan Pengelolaan Sampah Berbasis Sumber - Yudistira Adnyana; Sri Sulandari; IW. Astawa (Ekuitas: Jurnal Pendidikan Ekonomi, 2023)
The waste problem needs to be overcome because it threatens health , environment and tourism in Bali. The ability to manage waste by the government and the community has not been optimal. The government is trying to overcome the waste problem through policies. The problems are, (1) How is the implementation of source-based waste management policy in Penatih Dangin Puri Village? (2) What are the obstacles in implementing source-based waste management policies in Penatih Dangin Puri Village? The problem is analyzed with the theory of implementation model of Syahrul Mubarok et al (2020) which states that policy implementation is influenced by 3 aspects: policy content, policy context and policy process. Using qualitative research methods. The results showed that the village government had implemented a source-based waste management policy. From the aspect of policy content, Penatih Dangin Puri Village has implemented source-based waste management. Conclusions, 1) Governor’s regulation Number 47 of 2019 has been implemented in Penatih Dangin Puri Village but has not been optimal. 2) Obstacles in implementing Governor’s regulation number 47 of 2019 include: communication, resources and bureaucratic structure.